2020
DOI: 10.23887/jpi-undiksha.v9i1.20884
|View full text |Cite
|
Sign up to set email alerts
|

Items Quality Analysis Using Rasch Model To Measure Elementary School Students’ Critical Thinking Skill On Stem Learning

Abstract: Critical thinking as one of the 21st century competences required by students needs to be developed and analyzed by employing qualified assessment instrument. Test is a kind of critical thinking assessment instrument which quality is developed and analysed to create a meaningful learning. A total of 10 multiple choices items were developed based on critical thinking indicators. The items were then given to forty two 4th grade students in one of the elementary schools in Tasikmalaya-West Java after obtaining ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 10 publications
2
25
0
5
Order By: Relevance
“…The stages of the analysis process are through Rasch modeling with the adaptation of stages carried out by (Hamdu et al, 2020) The stages of the data collection and analysis process are presented in Figure 1. Data collection begins with the implementation of learning activities as the cause of the results of acquiring HOTS abilities in students.…”
Section: C4 Analysismentioning
confidence: 99%
“…The stages of the analysis process are through Rasch modeling with the adaptation of stages carried out by (Hamdu et al, 2020) The stages of the data collection and analysis process are presented in Figure 1. Data collection begins with the implementation of learning activities as the cause of the results of acquiring HOTS abilities in students.…”
Section: C4 Analysismentioning
confidence: 99%
“…Penilaian pembelajaran memberikan informasi yang baik bagi guru untuk membantu siswa belajar lebih baik. Selain alat dari pendekatan Teori Uji Klasik (CTT) yang biasa digunakan oleh guru, pendekatan lain yang disebut pengukuran objektif yang didasarkan pada probabilitas adalah alat alternatif yang dapat memberikan pengukuran yang lebih tepat (Hamdu et al, 2020). Model Rasch yang menyediakan teknik analisis psikometrik dapat digunakan oleh guru untuk mengembangkan item tes dan untuk menyajikan informasi yang relevan terkait dengan penilaian pembelajaran siswa (Sumintono, 2018).…”
Section: Pendahuluanunclassified
“…(Sumintono, 2015) Hasil dari data ini dapat memberikan informasi kepada guru untuk mengidentifikasi keterampilan dan kecocokan siswa dalam mengembangkan keterampilan berpikir kritis selama proses pembelajaran berbasis STEM. (Hamdu et al, 2020) Maka, dari hasil analisis tersebut, seorang guru akan lebih mudah untuk memberikan attention sesuai dengan ablitas dari siswa. Selain itu guru akan lebih mudah untuk melakukan koreksi pada soal yang telah di buat agar tidak membuat soal dengan kesalahan yang sama.…”
Section: Pembahasanunclassified
“…Other than that, Walker (Redhana, 2013) explains that thinking critically is a creative process that can drive the students to get new knowledge bypassing several problem solving and collaboration. Meanwhile, thinking critically is included in the process of thinking carefully thus it can help someone to create, evaluate, and make decisions on what is believed and done (Cáceres et al, 2020;Hamdu et al, 2020) . In a nutshell, thinking critically is a skill of knowledge process and skills that are used to solve the appearing problems, make decisions, and analyze any other possibilities and do research from the gained data and information, so that it produces information and conclusion that are wanted.…”
Section: Introductionmentioning
confidence: 99%
“…But there are still many teachers who have not been able to implement the 2013 curriculum in the learning process properly, especially in Mathematics. Teachers are still not ready to implement the 2013 curriculum (Cáceres et al, 2020;Hamdu et al, 2020). Based on the observation result that was done in elementary schools (SD) at Gugus VI Sukasada Sub-district, it is concluded that there are several problems which are there is a lack of students' ability and there is still lack of students' willingness in learning Math.…”
Section: Introductionmentioning
confidence: 99%